APPLICATION OF FAILURE MODE AND EFFECT ANALYSIS (FMEA) AND ISHIKAWA DIAGRAM IN DETERMINING THE DAMAGE ASPECTS AND MAINTENANCE PLAN OF SCREW FEEDER OF STEAM POWER PLANT COMPANY - Riszal, Ahmad; Yohanes, Eko; Risano, A Yudi Eka; Ibrahim, Fauzi; Supriadi, Harnowo; Zulhanif (Journal of Applied Science, Engineering and Technology, 2022)
Screw feeder is a type of material transporter that is widely used in various industrial sectors, where its function is very helpful in facilitating work, such as transporting very large amounts of material and this screw feeder has the advantage of long or sustainable tool operation. In industry, damage often occurs erratically and must undergo component replacement that is not in accordance with the routine maintenance schedule. In designing this maintenance machine, Ishikawa diagrams are used to analyze the causes and effects of component damage to the screw coal feeder, while to analyze other damage parameters and scheduling maintenance and planned component replacements, the Failure Mode and Effect Analysis (FMEA) method can be used. The results of this study indicate that the cause of the damage consists of several factors including humans, machines, materials, and methods. The actions that must be taken on the components include checking for wear and lubrication so that these components are always in good use. Based on the results of the calculation of the reliability of the screw coal feeder machine, the reliability of the screw feeder leaf component is 95.3% and the screw feeder casing component is 94.6%. This can also be seen from the mean time between failure (MBTF) for the leaf screw feeder component of 116.66 hours and the MBTF for the casing screw feeder component of 142.85 hours. With the application of the Ishikawa diagram and FMEA on the screw coal feeder maintenance system at steam power plant company (PLTU) PT XYZ in Indonesia. The maintenance implementation aims for a better planned. The actions that must be taken on the components include checking for wear and lubrication so that these components are always in good use. Based on the results of the calculation of the reliability of the screw coal feeder machine, the reliability of the screw feeder leaf component is 95.3% and the screw feeder casing component is 94.6%. This can also be seen from the mean time between failure (MBTF) for the leaf screw feeder component of 116.66 hours and the MBTF for the casing screw feeder component of 142.85 hours. With the application of the Ishikawa diagram and FMEA on the screw coal feeder maintenance system at PLTU PT XYZ, the maintenance implementation becomes better planned. The actions that must be taken on the components include checking for wear and lubrication so that these components are always in good use. Based on the results of the calculation of the reliability of the screw coal feeder machine, the reliability of the screw feeder leaf component is 95.3% and the screw feeder casing component is 94.6%. This can also be seen from the mean time between failure (MBTF) for the leaf screw feeder component of 116.66 hours and the MBTF for the casing screw feeder component of 142.85 hours. With the application of the Ishikawa diagram and FMEA on the screw coal feeder maintenance system at PT XYZ, the maintenance implementation becomes better planned. the reliability of the screw feeder leaf component is 95.3% and the screw feeder casing component is 94.6%. This can also be seen from the mean time between failure (MBTF) for the leaf screw feeder component of 116.66 hours and the MBTF for the casing screw feeder component of 142.85 hours. With the application of the Ishikawa diagram and FMEA on the screw coal feeder maintenance system at PT XYZ, the maintenance implementation becomes better planned. the reliability of the screw feeder leaf component is 95.3% and the screw feeder casing component is 94.6%. This can also be seen from the mean time between failure (MBTF) for the leaf screw feeder component of 116.66 hours and the MBTF for the casing screw feeder component of 142.85 hours. With the application of the Ishikawa diagram and FMEA on the screw coal feeder maintenance system at PT XYZ, the maintenance implementation becomes better planned.